Rare bird documentation form for Lesser Black-backed Gull in the Cedar River at Cedar Rapids, 1993 - Wickham, Peter P.et al (1993)
Rare bird documentation form for a Lesser Black-backed Gull in the Cedar River at Cedar Rapids in Linn County, IA on December 18, 1993. Epson - sheet feed